An evolving database for Quaternary aminostratigraphy. (June 2015) - Wehmiller, John F.; Pellerito, Vincent
Abstract : Highlights: Overview of amino acid racemization research, Quaternary coastal sites. Database design, structure and function, amino acid racemization data. Quaternary geochronological methods: U-series, racemization, radiocarbon. Abstract: Amino acid racemization (AAR) dating methods have been used since the mid-1960s. Since that time, information technologies have evolved as AAR laboratories have worked to appropriately catalog sample collections and analyses. The University of Delaware AAR Database (UDAARDB) is a database of AAR and other geochronological data from coastal Quaternary sites in North and South America that has been in development for over 25 years. In that time, database and software platforms have changed and a concerted effort has been made to digitize legacy data for preservation and to make these data available for future use. To ensure data preservation, all or part of UDAARDB is redundantly hosted at three institutions as data files and maps. Furthermore, the flexible nature of accessing the data (i.e., as online maps and common format data files) helps to maintain a public presence and, therefore, assists in their preservation.